A analysis Hedonism in the Film Sudden Rich Work Anggy Umbara Literary Sociology Studies (PT. LARPA JAYA PUBLISHER, 2023)
Study aim For know problem social form poverty , crime , and disorganization family in the film Mendadak Kaya Karya Anggy Umbara with approach literary sociology . Research data sources This is the film Sudden Kaya masterpiece Anggy Umbara with The duration of the film is 1 hour 32 minutes and is produced by MD Pictures. Research data This is whole the contents of the film Mendadak Kaya Karya Anggy Umbara in it there is problem social form poverty , crime , and disorganization family . Method study This is method descriptive with use approach qualitative . Instrument study This done with procedure observation and documentation . Data analysis techniques in the form of watching movies over and over again , understanding , collecting data , tagging every minutes , describe and conclude . Research results This can answer from the research statement that there are social problems in the form of poverty, crime, and family disorganization with a literary sociology approach. The data obtained from social problems in the form of poverty is 13 data, crime problems are 8 data, and family disorganization problems are 4 data. It can be concluded that there are social problems in the form of poverty, crime, and family disorganization in the film Mendadak Kaya by Anggy Umbara with a sociology of literature approach.